Development of indicators to assess the quality of nursing care in Thailand - Kunaviktikul W. (2014)
In Thailand, quality of nursing care has been defined. The next step is to determine how to measure quality. Given the limited resources to provide health care and the demands to justify the use of registered nurses, there is an urgent need to demonstrate how professional nursing care makes a difference to outcomes of care. The purpose of this study was to further refine nursing indicators of quality by developing operational definitions, validating them and then determining their applicability in a variety of clinical settings. The process included three phases. The first phase used focus groups to identify and define indicators of quality nursing care and the second phase included testing these indicators in four settings to determine if data could be collected. Manuals were developed that defined the quality indicators and the scoring system to be used in the assessment. In the third phase, the findings were presented to a group of experts and minor changes were made to the indicators. Then, the indicators were categorized into three groups: structure, process, and outcome. The validated outcomes and manual for their assessment and monitoring were sent to all hospitals in Thailand. The study relied upon the findings from the four different hospitals. If the indicators were implemented in a wider variety of settings, other differences might have emerged. There is also a possibility that 'best practice' might not be reflective of the scientific basis of nursing practice. The findings generally support the initial work carried out in the USA. There is a need to continue to study how these indicators can improve patient outcomes. © 2005 Blackwell Publishing Asia Pty Ltd.